Fan-Based Learning in Language Education. - Rey-Godoy, Sergio; Vazquez-Calvo, Boris (My University, 2025)
Conceived as an open educational resource, Fandom and Language Education is a nine-episode micro-series (≈ 5 min each) that shows how everyday fan activities become meaningful, low-cost language-learning tools—perfect for teachers, informal educators and content creators, andcurious fans. Recorded for YouTube (premiering May 2025) and archived on Zenodo under CC-BY 4.0, each episode mixes real learner stories, practical tips, and research-informed insights. Episode line-up 1. Introduction to fandom and language education: how global fan communities turn passion into language practice 2. Fanfiction in language learning: writing, reading, and feedback loops that build fluency 3. Fansubs and fan translations: multilingual subtitles and crowd translations as authentic scaffolds 4. Cosplay and conventions: face-to-face conversation and intercultural exchange in fan spaces 5. Fandom-driven motivation: why passion sustains long-term language study 6. Fan art for visual and written expression: art made by fans 7. Podcasts, vlogs and other fan media: listening and speaking through user-generated content 8. Challenges and ethics: plagiarism, misinformation, slang, and best practice 9. Conclusion and open resources: AO3, Viki, Duolingo, Discord and more for lifelong learning By centering passion-based communities—writing fanfic, subtitling shows, crafting cosplay—Fandom and LanguageEducation demonstrates that meaningful, motivating language practice thrives where creativity and collaborationintersect. Share it, remix it, or screen it in class: the series is yours to use.
Conceptualization Educational vision, fan-learning focus — Sergio Rey-Godoy; Boris Vázquez-Calvo Methodology Pedagogical framework and activity design — Sergio Rey-Godoy Investigation Gathering case studies and research sources — Boris Vázquez-Calvo Writing – original draft Episode scripts — Boris Vázquez-Calvo Writing – review & editing Script refinement and clarity checks — Sergio Rey-Godoy Visualization Storyboards, motion graphics, illustrations, overall visual style — Sergio Rey-Godoy Software Audacity (audio capture & cleanup); Canva Pro (graphics & video layout); ChatGPT (wording assistance) — Sergio Rey-Godoy Resources Voice-over narration — Sergio Rey-Godoy; Boris Vázquez-Calvo Data curation Captioning (auto-generated, reviewed by Sergio Rey-Godoy); asset archiving (Boris Vázquez-Calvo) Project administration Scheduling, asset management, production coordination — Boris Vázquez-Calvo Supervision Academic oversight — Boris Vázquez-Calvo Funding acquisition Grant writing & reporting — Boris Vázquez-Calvo Plan Propio de Docencia – “Ayuda para la elaboración de materiales en vídeo,” University of Málaga, Spain (€2 000) Research project DEFINERS – Digital Language Learning of Junior Language Teachers (TED2021-129984A-I00), funded by the Spanish Government MCIN/AEI/10.13039/501100011033 and the EU NextGenerationEU/PRTR Other Special thanks to fan communities, participating learners, and researchers from the DEFINERS project. License: CC-BY 4.0 — feel free to reuse, remix, and share with attribution. CRediT note: Roles follow the Contributor Roles Taxonomy (https://credit.niso.org). When a task spans more than one role (e.g., video editing touches both Visualization and Software), it is listed under the role that best captures its primary scholarly contribution.
Keywords: Lenguas - Estudio y enseñanza; Aprendizaje; Redes sociales en internet; Alfabetización digital; Cultura popular; Innovaciones tecnoloógicas; Videojuegos; Fans; Enseñanza - Innovaciones; Aprendizaje informal de lenguas; Language learning; Language teaching; Language education; Social media; Fandom; Fan; Fan practices; Popular culture; Informal learning; Informal language learning; Digital literacy; Digital technology; Video game